Implementasi Asas Perlindungan Konsumen Dalam Sektor Pangan Berdasarkan Undang-Undang No. 8 Tahun 1999 Tentang Perlindungan Konsumen - Qoyyumi Permadi*, Shafira Andiena; Lewiandy, Lewiandy (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
In meeting their daily needs, of course humans are regular consumers to meet their basic needs. For this reason, all human activities require legal protection to ensure that their rights and obligations are fulfilled. Consumer protection is all the governments efforts to ensure legal certaintly to provie protection to consumers. Consumer protection in the food sector has a very important role in ensuring that the products consumed by the public are high grade, safe and meet established health standards. Consumer protection is of course based on the principles of benefits, fairness, balance, consumer security and safte, as well as legal certaintly. If business actors, especially in the food sector, do not implement the principle of consumer protection properly, of course the welfareof society or consumers will not be achived. The method used in this research is normative legal research by identifying positive laws that apply in Indonesia. The aim of this research is that it is hoped that business actors in the food sector can apply the principles of consumer protection well in order to create a healthy, high quality and safe food environment and provide benefits to public health and the stability of the food industry. The results of this research can be concluded that through good implementation of the principles of consumer protection in the food sector, it will provide long term benefits that can be received by all related parties.